The development of a micro-teaching module for online learning - Megawati Megawati; Winda Trisnawati (Lighthouse Publishing, 2022)
The purpose of this research was to develop a module of micro teaching-based technology for online learning for students at STKIP Muhammadiyah Muara Bungo and to analyze the module's validation and appropriateness for online learning. The development procedures for this research utilized a 4-D model (Define, Design, Develop, and Disseminate), as demonstrated by the validation analysis conducted with learning material experts, learning media experts, and students. The average score for all aspects combined is 82.6. It demonstrates an excellent category. This means that the microteaching module in online learning serves as instructional material for improving teaching ability through the use of technology. The microteaching online learning module is valid and appropriate for use.